PENDAMPINGAN TEKNIS MASYARAKAT DESA SIRNAJAYA DALAM MENGHADAPI RISIKO BENCANA TANAH LONGSOR - Iit Adhitia; Wahyu Gendam Prakoso; Irfan Marwanza; Muhammad Agus Kamardi; Singgih Irianto Trisilo Hadi; Solihin (Universitas Trisakti, 2023)
The hilly area around Situ Rawa Gede is located in Sirnajaya Village, Sukamakmur District, Bogor Regency, with the existence of Situ Rawa Gede surrounded by hills extending from the south to the northwest. Landform changes are increasingly visible in the hilly areas around Situ Rawa Gede due to community gardening activities and coffee agro-tourism, and the opening of settlements causes topsoil to peel off, which is detrimental to the physical condition of the soil, can cause erosion and trigger mass movement of soil/rock. It is necessary to arrange land in the hilly area around Situ Rawa Gede to be appropriately organized. A zoning map of the vulnerability of ground motion is needed; from this map, it can be seen which areas have low to high soil vulnerability. Land management is one of them by making terracing which helps increase water infiltration into the soil and limiting surface runoff to minimize the risk of surface water erosion. This PkM activity provides a technical description of the concept of making a soil movement vulnerability zoning map to the community so that they understand the importance of maps of low to high soil vulnerability zones in their area in disaster mitigation efforts and through technical assistance related to the application of bench terraces and garden terraces so that they can be planted with plantation crops as ground cover is also for the safety of the community and visitors to coffee agro-tourism.